2010
DOI: 10.1177/1753193410387329
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe hand wounds with integra® dermal regeneration template

Abstract: We report our experience with the use of Integra® for the management of severe traumatic wounds of the hand. Fifteen patients were treated with follow-up ranging from 10 to 37 months. Wounds were associated with an osseous and/or joint and/or tendon exposure. Following Integra® placement, patients were managed with dressings and subsequent split-thickness skin grafting an average of 26 days later. Integra® was successful in achieving durable, functional and aesthetic definitive coverage in 13 of 15 application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 18 publications
0
45
1
3
Order By: Relevance
“…In both cases, the disruption of both neurovascular bundles and dorsal vascular support led to necrosis of the distal phalanx [9]. Other authors have reported cases of burn injuries to the hands [10] and reconstruction of digital defects [7] that have been successfully managed with acellular dermal matrices (ACMs).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In both cases, the disruption of both neurovascular bundles and dorsal vascular support led to necrosis of the distal phalanx [9]. Other authors have reported cases of burn injuries to the hands [10] and reconstruction of digital defects [7] that have been successfully managed with acellular dermal matrices (ACMs).…”
Section: Discussionmentioning
confidence: 97%
“…Applied to wound beds with adequate blood supply, such as the paratenon, and through the revascularization of the scaffold, it provides a new vascular layer. This makes it a useful therapeutic tool in situations where a flap cover would normally be required [7].…”
Section: Introductionmentioning
confidence: 99%
“…Collagen Substitutes . The use of bovine collagen dermal substitutes is increasing and will become an important factor in wound healing in the future [ 9 ]. See the Chapter on Burns.…”
Section: Cosmesis Of the Primary And Secondary Defectsmentioning
confidence: 99%
“…In patients with acute burns and in patients with chronic skin lesions, following severe injury in skin and peripheral nerves, a dermal substitute highly porous collagen scaffold has induced regeneration displacing the skin autografts in the treatment of skin lesions [11][12][13][14][15][16][17][18][19]. After severe trauma, in the adult mammal occurs a wound constriction and scar formation.…”
Section: Short Commentarymentioning
confidence: 99%